Study and Characterization of Copper and Titanium Oxides Nanostructures for Some Molecular and Biological Applications - Abdulazeez Alhamd, Omar; Ghazi Ali , Ghazwan; Salih Hasan Aljuboori, Mutaz (Trends in Sciences, 2024)
In this work, Copper and Titanium nanocomposites (NPs) were prepared by mixture exchange process with ratios (25, 50 and 75 % CuO-TiO2). The biological activity was studied, and it was found that the concentrations of 50 and 100 µg/mL of 50 and 75 % CuO-TiO2 were the best concentrations, Low concentrations of the nanoparticle mixture at 25 µg/mL also stimulated the growth of symbiotic bacteria. The mixture of nanoparticles was easier to prepare and more effective in inhibiting bacterial growth. biochemical test and PCR were performed to confirm the identity of the studied bacteria. While isolating the bacteria, a new type of bacteria was detected and registered in the Global Gen Bank under accession No. OP942239. Surface and structure properties have been studied using FESEM, EDS analysis, XRD and FTIR respectively. It can be seen that the size and diameter of the nanocomposite increase with the weight ratio of CuO-TiO2. The aggregated CuO-TiO2 nanostructures with different ratios were transformed gradually into a uniform spherical shape. The average size of the CuO/TiO2 composite was found to be about 32.122, 29.865 and 27.607 nm at 25, 50 and 75 % CuO-TiO2 respectively. While the mean sizes of CuO and TiO2 were 25.35 and 34.38 nm respectively. The crystalline size decreases after the ion exchange process, which could be due to the diffraction peaks being broad in all the samples of Copper Titanate at the surface. Subsequently, adding Copper particles to the TiO2 film can improve the performance of the material. HIGHLIGHTS The nanostructure CuO-TiO2 was created through various loading ratios. These NPs’ efficiency was calculated using a number of techniques, including FTIR, X-ray diffraction, EDS spectra, and FESEM. The observations indicate that molecular transition parameters play an essential role in determining the size, shape, and functionality of CuO- TiO2 NPs. The sharp peaks observed in the composites indicated higher crystallinity in CuO. In addition, two types of NPs have shown promising effects in inhibiting NPs aggregation and enhancing biological effects but the potential of these NPs against different bacteria may differ. Thus, further research and testing is needed to assess its efficacy and human health and environmental impact before considering its use. In conclusion, copper and titanium NPs have their distinct advantages in bacterial inhibition, and the choice between them should be based on specific conditions and environmentally friendly factors. GRAPHICAL ABSTRACT